The control of movement gradually transitions from feedback control to feedforward adaptation throughout childhood - Laura A. Malone; Nayo M. Hill; Haley Tripp; Vadim Zipunnikov; Daniel M. Wolpert; Amy J. Bastian (npj Science of Learning)
Abstract The ability to adjust movements in response to perturbations is key for an efficient and mature nervous system, which relies on two complementary mechanisms — feedforward adaptation and feedback control. We examined the developmental trajectory of how children employ these two mechanisms using a previously validated visuomotor rotation task, conducted remotely in a large cross-sectional cohort of children aged 3–17 years and adults (n = 656; 353 males & 303 females). Results revealed a protracted developmental trajectory, with children up to ~13–14 years showing immature adaptation. Younger children relied more on feedback control to succeed. When adaptation was the only option, they struggled to succeed, highlighting a limited ability to adapt. Our results show a gradual shift from feedback control to adaptation learning throughout childhood. We also generated percentile curves for adaptation and overall performance, providing a reference for understanding the development of motor adaptation and its trade-off with feedback control.